Karakteristik pengeringan pisang kepok berdasarkan ketebalan irisan dan proses bolak balik pada pembuatan pisang sale - Devi Tanggasari; Ariskanopitasari Ariskanopitasari; Chairul Anam Afgani (Jurnal Agrotek Ummat, 2023)
One of processed bananas that has a long shelf life is banana fritter. Banana fritter is made by slicing bananas in various thicknesses and then drying them. Drying intends to reduce or eliminate the water content in bananas. This study aims to determine the drying characteristics of kepok bananas based on the thickness of the slices and the back and forth process in making banana fritter. The design used in this study was a completely randomized design (CRD) with two types of thickness, namely 1 cm (K1) and 1.5 cm (K2) cm and there were once (B1) and twice (B2) alternating process treatments respectively in a day. Research data were analyzed using SPSS. The results showed that the degree of thickness (K) significantly affected the mass change of bananas during drying (P value = 0.0001), and the alternating process of bananas (B) did not affect the mass change of bananas during drying (P value = 0.532), while the combination between treatment B and K did not have a significant effect (P value = 0.385). From the results of this study it can be concluded that the thickness of the dried kepok banana slices greatly affects the characteristics of the resulting banana fritter. The drying rate and MR value are directly proportional to the amount of moisture in the banana during drying which is shown at a thickness level of 1.5 cm, so it is advisable to carry out further research mechanically with a thickness level of 1.5 cm kepok banana slices.